2010
DOI: 10.1016/j.juro.2009.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Radical Cystectomy for Bladder Cancer: Surgical and Pathological Outcomes in 100 Consecutive Cases

Abstract: We report a relatively large and maturing experience with robotic radical cystectomy for the treatment of bladder cancer providing acceptable surgical and pathological outcomes. These results support continued efforts to refine the surgical management of high risk bladder cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
78
1
9

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(93 citation statements)
references
References 22 publications
4
78
1
9
Order By: Relevance
“…In various series lesser amount of perioperative blood loss, and decrease in hematocrit levels were indicated when compared with open surgery with an average blood loss ranging between 273, and 473 mL. [19,20] In our series average blood loss was 325 mL, and drop in hematocrit was 3.15% which were within acceptable limits.. As for hospital stays, we think that for a major surgery 12 days should not be considered as a prolonged hospital stay, and as experiences accumulate, lymphatic drainage which develops after lymphadenectomy may be prevented, and drain withdrawal, and discharge times may be performed at an earlier date. Therefore conduction of a randomized study which will compare open, and robotic surgery will be more appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…In various series lesser amount of perioperative blood loss, and decrease in hematocrit levels were indicated when compared with open surgery with an average blood loss ranging between 273, and 473 mL. [19,20] In our series average blood loss was 325 mL, and drop in hematocrit was 3.15% which were within acceptable limits.. As for hospital stays, we think that for a major surgery 12 days should not be considered as a prolonged hospital stay, and as experiences accumulate, lymphatic drainage which develops after lymphadenectomy may be prevented, and drain withdrawal, and discharge times may be performed at an earlier date. Therefore conduction of a randomized study which will compare open, and robotic surgery will be more appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…The question naturally arises then, can a new procedure like RARC achieve results with same or better oncological and functional success than ORC? Pruthi and his team followed a total of 100 consecutive patients who underwent SCRRC from 2006 to 2009 for clinically localized bladder cancer [26]. Pruthi et al found that in no SCRRC procedure was there a positive surgical margin and 8% of patients subsequently suffered a major complication (Clavien grade 3 or higher) [26].…”
Section: Oncological Outcomesmentioning
confidence: 99%
“…Pruthi and his team followed a total of 100 consecutive patients who underwent SCRRC from 2006 to 2009 for clinically localized bladder cancer [26]. Pruthi et al found that in no SCRRC procedure was there a positive surgical margin and 8% of patients subsequently suffered a major complication (Clavien grade 3 or higher) [26]. At a mean followup of 21 months, 15 patients had disease recurrence with 6 eventually succumbing to the disease [26].…”
Section: Oncological Outcomesmentioning
confidence: 99%
See 2 more Smart Citations